Gene Targets Network Analysis for the Revealing and Guidance of Molecular Driving Mechanism of Lung Cancer - Huang, Risheng; Xiang, Xiao; Zhang, Kangliang; Zheng, Yuanliang; Wang, Chichao; Hu, Guanqiong (Frontiers in Genetics, 2021)
The objective was to explore the function of gene differential expressions between lung cancer tissues and the interaction between the relevant encoded proteins, thereby analyzing the important genes that were closely related to lung cancer. 120 samples from the GEO database (including two groups, i.e., 60 lung cancer in situ specimens and 60 normal specimens) were taken as the research objects, which were submitted to the analysis of signaling pathway, biological function enrichment, and protein interactions to reveal the molecular driving mechanism of lung cancer. Results: A total of 875 differentially expressed genes, including 291 up-regulated genes and 584 down-regulated genes, were obtained by analyzing the samples. The up-regulated genes mainly participated in the biological processes including protein metabolism, proteolysis, mitosis, and cell division. The down-regulated genes mainly participated in the process of neutrophilic granulocyte chemoattractant, inflammatory reaction, immune response, and angiogenesis. The up-regulated genes were mainly enriched in cell cycle, extracellular matrix receptor interaction, protein digestion and absorption, p53 signaling pathway, and starch and sucrose metabolism. The down-regulated genes were mainly enriched in chemokine signaling pathway, malaria, tumor necrosis factor signaling pathway, cell adhesion molecule, and African trypanosomiasis pathway. Therefore, the TOP2A, CCNB1, CCNA2, CDK1, and TTK might be the critical target genes of lung cancer. Protein expressions of high-expressed genes and low-expressed genes in patients were higher than those of the control group. The protein corresponding to the high-expressed genes was expressed higher in the patient group; at the same time, the protein corresponding to the low-expressed genes was also expressed in the patient group, suggesting that even though the proteins corresponding to low-expressed genes were low-expressed in patients, they were still the lung cancer-related target genes. In conclusion, the molecular driving mechanism in lung cancer was mainly related to protein metabolism, proteolysis, mitosis, and cell division. It was found that TOP2A, CCNB1, CCNA2, CDK1, and TTK might be the critical target genes of lung cancer.